Pendidikan KARAKTER MELALUI PENDIDIKAN AGAMA ISLAM di SEKOLAH DASAR ISLAM TERPADU DI KOTA YOGYAKARTA - A.M. Wibowo (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
The study aims to (1) describe the model curriculum of religious education in Islamic integrated elementary schools (SDIT) at Yogyakarta, (2) described the implementation of religious education in Islamic Integrated Primary School in forming the religious character of the learner. (3) describe the support and constraints faced by Islamic integrated elementary schools in preparing and developing the religious education curriculum andits implementation in learning activities, (4) show the concept ideal model of Islamic religious education in Islamic integrated elementary schools. By using qualitative approach this research had found four things: (1) the model curriculum of Islamic education at SDIT is integrated in each unit subjects. (2) the implementation of religious education in and instilling religious character learners performed with variety of approaches like fullday school, habit forming, communicative stimulative, learning by doing, human approach, and leadership (3) The support factors to instilling of religious education curriculum character are factual and hidden curriculum, extra curriculum, programs habituation, and learning approaches used. While the obstacles are faced by infrastructure, cost of education, as well as the participation of parents who still feels less.